Respuesta :

Answer:

Question one solution: (-5,4)

Question two solution: (3,1)

Step-by-step explanation:

Remark

Both of these work better with substitution. When a y (or x) in two equations sits by itself on one side of the equation, substitution is the method of choice.

These two questions are a perfect example of when you can use substitution. You have "y"s sitting on one side of the equation alone and without coefficients.

y = -2x - 6

y = -2x - 6

y = x + 9

The "y"s must be equal when you are finished so they can be equated.

x + 9 = - 2x - 6                       Add 2x to both sides

x + 2x + 9 = -2x + 2x -6        Combine like terms

3x + 9 = - 6                            Subtract 9 from both sides

3x + 9 - 9 = - 6 - 9                 Combine

3x = - 15                                 Divide by 3

3x/3 = - 15/3                           Do the division

x = - 5

============================

Now solve for y

y = x + 9

y = -5 + 9

y = 4

y = - x + 4

y = - x + 4

y = 5x - 14

Equate the y's

5x- 14 = -x + 4               Add x to both sides

5x + x - 14 = -x + x + 4    Combine

6x - 14= 4                       Add 14 to both sides

6x - 14 + 14  = 4 + 14      Combine

6x = 18                           Divide by 6

6x/6 = 18/6                    Do the division

x = 3

============================

Solve for y

y = -x + 4

y = -3 + 4

y = 1